Growth Rate and Mortality of Giant Freshwater Prawn (Macrobrachium rosenbergii) In Kuala Cenaku Village, Riau Province - Ade Hermawita; Muhammad Fauzi; Deni Efizon; Windarti Windarti (Jurnal Perikanan dan Kelautan, 2022)
The growth rate and mortality rate of giant prawns (Macrobrachium rosenbergii) in the Kuala Cenaku River, Indragiri Hulu Regency, Riau Province were carried out based on carapace length frequency data collected from May to July 2020. This study aims at the growth rate and mortality of giant prawns in the Kuala Cenaku River. For estimating dynamic population, data were analysed by using FiSAT II. The growth parameter of tiger shrimp was 0,78/year with carapace asymptotic length (L) of 84,8 mm, total mortality rate (Z), natural mortality rate (M), fishing mortality rate (F) were 2,35/year and 1,16/year, 1,19/year, respectively, while and exploitation rate (E) estimated 0,50. The exploitation rate of Tiger Freshwater Prawn in Kuala Cenaku River was fully exploited and tend to overexploited so that it needed to manage wisely and carefully